Performance evaluation of noma in wireless communications - Nguyễn Thị Thu Thảo; Nguyễn Hoàng Tú; Hồ Nhựt Minh; Đỗ Duy Tân; Trương Quang Phúc (Journal of Technical Education Science, 2021)
This paper studies the performance of Non-Orthogonal Multiple Access Technique (NOMA), which is effectively applied in 5G and a potential candidate in 6G. The performance of NOMA is assessed in terms of bit error rate (BER), data rate, and outage probability (OP), which are obtained through various simulation results in Matlab considering Rayleigh fading channels influenced by Additive White Gaussian Noise (AWGN) in both perfect Successive Interference Cancellation (SIC) and imperfect SIC. In general, as the transmit power increases, the data rate value increases accordingly while the BER and OP values are significantly improved. The analytical results show that NOMA provides a good foundation for the development of techniques that contribute to improving quality of service for future (wireless) communication systems.